Synthesis and Characterization of Schiff Base Compound Benzaldehyde- 2,4-Dinitrophenylhydrazone as a Carbonate Anion Sensor - Musyrifah, Arina; Hidayati, Nurlisa; Yuliasari, Nova (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Benzaldehyde-2,4-dinitrophenylhydrazone was synthesized via the condensation of benzaldehyde with 2,4- dinitrophenylhydrazine. The product was analyzed using UV–Vis and FT-IR spectroscopy, and its solvatochromic properties were investigated in DMF, acetone, and ethanol. Its application as a carbonate anion sensor was evaluated under optimized conditions. Schiff base formed orange crystalline solids with a 91.86% yield. UV-Vis spectra showed maximum absorption wavelength at 260 nm (π-π*) and 390 nm (n-π*). FT-IR analysis proves the presence of azomethine band (HC=N) at 1618 cm-1 and the shift of the N-H stretching band region from 3325 to 3284 cm-1. Among the solvents studied, DMF exhibited the highest solubility and color stability, acetone showed the greatest absorbance but poor stability, and ethanol showed low solubility with the formation of a precipitate. Functioning as a carbonate anion sensor, the Schiff base exhibited a noticeable color change from yellow to red, along with a bathochromic shift from 390 nm to 495 nm (π→π*), reaching its maximum response after 30 minutes.